A Systematic Review of Validity and Reliability of Perceived Exertion Scales to Older Adults - Paula Born Lopes; Luana Loss Cabral; Robert J Robertson; Andrea Holtz Franco; Gleber Pereira, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Rating of perceived exertion (RPE) scales have been used to monitor and to prescribe exercise intensity of older adults, although many scales have not determined the validity and reliability of this population. The aim of this study was to evaluate the cross-cultural adaptation, validity, and reliability of RPE scales applied to older adults. We performed the systematic search of the articles in March 2020 and included Web of Science, Scopus, PsycInfo, PubMed, Virtual Health Library, and Science Direct databases. We limited the search to the English language, with no year restriction. A modified McMaster (1998) critical appraisal tool determined the level of quality assessment in each included study. Forty-four papers met the inclusion criteria and there were 5 different RPE scales that had been used with older adults. A lower score in methodological quality was found to scale application (i.e., definition, instruction, or familiarization) and there was no consensus about the instructions to use RPE scales. The Borg 6-20 was the more suitable tool for controlling exercise in older adults, due to its validation and cross-cultural adaptation for older adults. Thus, the results of this systematic review demonstrate the need for studies performing a cross-cultural adaptation of other RPE scales to different languages and their validity and reliability under different exercise conditions when considering older adults’ evaluations.